Advancing eHealth in Society 5.0: A Fuzzy Logic and Blockchain-Enhanced Framework for Integrating IoMT, Edge, and Cloud With AI - Joy Dutta; Deepak Puthal (IEEE Access)
Society 5.0 envisions a human-centered society where advanced technologies seamlessly integrate to enhance quality of life, particularly in healthcare. To advance eHealth within this vision, we present a comprehensive framework that integrates the Internet of Medical Things (IoMT), edge computing, and cloud services with Explainable Artificial Intelligence (XAI) and blockchain technology, customized for the 6G era. We introduce the Health Prediction using Cloud Edge 2.0 (HPCE 2.0) algorithm, which employs fuzzy logic to effectively combine historical Electronic Health Records (EHRs) with real-time IoMT data, providing precise and personalized health severity level predictions. To ensure data integrity and security, we integrate the Proof of Authentication 2.0 (PoAh 2.0) consensus mechanism within a blockchain-enhanced IoMT-Edge-Cloud framework. A case study on predicting cardiac arrest in elderly patients demonstrates the practical effectiveness of our framework. Utilizing XAI models such as LIME and SHAP, we provide both local and global explanations for AI predictions, enhancing transparency and trust in healthcare applications; counterfactual explanations offer actionable insights for patients to proactively manage health risks. Security assessments confirm efficient block formation and verification times, validating the system’s scalability and compliance with stringent security standards. This work sets a new standard in digital healthcare by aligning technological advancements with ethical considerations, fostering a human-centered approach consistent with Society 5.0’s vision. Harnessing the capabilities of emerging 6G networks, our framework paves the way for more responsive, secure, and interpretable AI-driven healthcare solutions.